If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(x + 9) + 10x = -34 Reorder the terms: 3 + -1(9 + x) + 10x = -34 3 + (9 * -1 + x * -1) + 10x = -34 3 + (-9 + -1x) + 10x = -34 Combine like terms: 3 + -9 = -6 -6 + -1x + 10x = -34 Combine like terms: -1x + 10x = 9x -6 + 9x = -34 Solving -6 + 9x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 9x = -34 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = -34 + 6 9x = -34 + 6 Combine like terms: -34 + 6 = -28 9x = -28 Divide each side by '9'. x = -3.111111111 Simplifying x = -3.111111111
| 3z^2+2z=4z-5 | | (1/4)+(3/8)x=(3/4) | | 8b+3+10b=2(2b-2)+3 | | 12b^4+3b+24=0 | | 3(t+5)+5(2t+8)=12(t+2)+2 | | 2/7-(1/7)=3/14 | | 7a/30*15/1 | | -10-3r=1+8r | | 1/2x+2=8x+7/8 | | x*(540/x)=540 | | 5f^2-8f+3=0 | | 5+3(42-12)/9 | | 63=-7x-9y | | 5x+20=-2 | | -3(x+2)+5=-9 | | (1/2)t+(1/3)=10 | | 4x-4+8x+12=2x-8+6x | | 8a-b-3a+4b= | | x(2-5x)=12-6x-5x^2 | | 5-x/3+x=13/12 | | 3y+5=9x | | 1.5x+9=4x-6 | | 7y^2-10y=0 | | 3(w-9)-(-7w-5)=9w | | 7(x-6)=15 | | 1/4x7=2 | | 6=12+h/-7 | | -5x+1/2x=-4 | | 7-(3--m)=8 | | 11=10x-9 | | 1/4x7=20 | | 3(10x-2)=-4(x-3) |